2014
DOI: 10.1016/j.matbio.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan modulates angiogenesis and bone formation during fracture healing

Abstract: Matrix proteoglycans such as biglycan (Bgn) dominate skeletal tissue and yet its exact role in regulating bone function is still unclear. In this paper we describe the potential role of (Bgn) in the fracture healing process. We hypothesized that Bgn could regulate fracture healing because of previous work showing that it can affect normal bone formation. To test this hypothesis, we created fractures in femurs of 6-week-old male wild type (WT or Bgn+/0) and Bgn-deficient (Bgn-KO or Bgn−/0) mice using a custom-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 35 publications
3
68
0
Order By: Relevance
“…Our results revealed that biglycan is involved in regulating malignant transformation by up-regulation of VEGF. The results were consistent with previous findings, which reported that the VEGF expression is reduced in biglycan knockout mice [27].…”
Section: Discussionsupporting
confidence: 94%
“…Our results revealed that biglycan is involved in regulating malignant transformation by up-regulation of VEGF. The results were consistent with previous findings, which reported that the VEGF expression is reduced in biglycan knockout mice [27].…”
Section: Discussionsupporting
confidence: 94%
“…We show here that FGFR3 and BGN are expressed in the fetal bone tissue in neighboring cellular compartments in analogy to the testis, supporting a possibility of an interaction. The fact that both proteins have been described in relation to bone growth, albeit with opposing effects; FGFR3 as a growth inhibitor and BGN as a growth inducer (Berendsen et al, 2013;Chen et al, 2004;Colvin et al, 1996;Miguez et al, 2011;Parisuthiman et al, 2005;Qi et al, 2014;Xu et al, 1998), underlines the potential importance of these binding partners in relation to bone development as well.…”
Section: Discussionmentioning
confidence: 99%
“…BGN, constitutively expressed in normal endothelial cells, becomes significantly overexpressed in tumor tissues and promotes the migration of endothelial cell and neovascularization of cancer [28]. With similar mechanisms, BGN is able to triggering VEGF synthesis in tumor cells, and it has been shown to bind and sequester (VEGFA) in the ECM, thus generating a reservoir of VEGF that can be released during ECM degradation that associated with tumor, capacitating angiogenesis [29]. Moreover, neovascularization is closely related with ROS and TLR2 signaling.…”
Section: Discussionmentioning
confidence: 99%